The Influence of Lesson Planning, Teaching Methods, and Assessment Instruments on the Pedagogical Competence of Microteaching Student Teachers at FEB UNY - Ali Muhson; Kiromim Baroroh; Tejo Nurseto; Ahmad Chafid Alwi; Pangestika, Ratna Rosita (Sinergi International Journal of Education, 2025)
The study employs Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze measurement validity, reliability, and structural relationships among variables within a theoretically grounded framework. An integrated structural model is proposed to examine three core instructional dimensions lesson planning, teaching methods, and assessment instruments using SEM. This approach addresses a methodological gap in microteaching research, which has predominantly relied on descriptive or quasi-experimental designs and has rarely examined latent variables or indirect effects. A quantitative explanatory design was implemented through a cross-sectional survey involving 169 microteaching students selected using proportional random sampling. Data were collected using validated Likert-scale questionnaires and analyzed with SEM-PLS. The results indicate that teaching methods have the strongest positive effect on pedagogical competence, followed by assessment instruments. Conversely, lesson planning demonstrates a significant but negative direct effect, suggesting that its influence on pedagogical competence may function indirectly through teaching methods and assessment practices. Furthermore, lesson planning and assessment instruments significantly affect teaching methods, highlighting the interdependence among instructional components. The study concludes that pedagogical competence develops through an interconnected system involving planning quality, instructional implementation, and assessment literacy. These findings emphasize the importance of integrative instructional design, authentic assessment training, and reflective teaching practices in microteaching. Overall, improving pedagogical competence requires the simultaneous development of planning, teaching, and assessment as mutually reinforcing elements of effective instruction.